Can you trust your car? [automotive electronics reliability testing]. - Berger, I.
Car electronics-especially those under the hood that control the throttle, the antilock brakes and other safety-critical systems-should work in kinds of weather. This paper describes how, to ensure reliability, carmakers test these electronics, and the cars, in special weather chambers
Keywords: Antilock brakes; Automotive electronics reliability testing; Safety-critical systems; Throttle control; Weather chambers